Integrating Value Stream Mapping, Waste Assessment Model, and Root Cause Analysis to Improve Loading–Unloading Efficiency at PT XYZ - Sulistyowati, Enik; Munawaroh, Madinatul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The loading and unloading process often becomes a bottleneck in the distribution of bottled drinking water due to excessive waiting time. This study aims to identify and minimize such delays using Value Stream Mapping (VSM). To strengthen the analysis, the Waste Assessment Model (WAM) was applied to examine the interrelationships among different types of waste, while Root Cause Analysis (RCA) was employed to uncover the main contributing factors. The study was conducted at a bottled water company experiencing significant delays in queuing and inspection stages. Following the implementation of improvement measures, time efficiency increased by 17.53%. The findings demonstrate that accurately identifying waste can enhance operational efficiency, streamline workflow, and enable the company to operate more productively.